Clinical and Epidemiological Correlates of Task-Specific Dystonia in a Large Cohort of Brazilian Music Players - Moura, Rita C.; de Carvalho Aguiar, Patrícia Maria; Bortz, Graziela; Ferraz, Henrique Ballalai (Frontiers in Neurology, 2017)
Musician’s dystonia is a task-specific dystonia (TSD) worldwide disabling disorder, and most of the affected individuals may have severe difficulty to play their instrument. Many professional music players may have to quit working as a player. The objective of the present study was to evaluate the clinical characteristics and frequency of TSD in Brazilian music players and to promote awareness of this condition among musicians. We visited orchestras and music schools delivering lectures on TSD and about the scope of our survey. Musicians were invited to answer a questionnaire, and those with possible neurological dysfunction associated with musical performance were recorded by video while playing the instrument. We visited 51 orchestras and music schools in 19 Brazilian cities between March 2013 and March 2015. We collected 2,232 questionnaires, and 72 subjects with suspicion of dystonia were video recorded during specific tasks and evaluated regarding motor impairment. Forty-nine individuals (2.2%) were diagnosed as having TSD (mean age 36.4 years; 92% male). The instruments most associated with TSD were acoustic guitar (36.7%) and brass instruments (30.6%). We concluded that Brazilian TSD music players are mainly male, classical music professionals, around 30 years of age, with arms, hands, or oromandibular muscles affected. TSD is a neurological condition that can impair musical performance and should receive more attention from musicians, teachers, and health professionals.